Evaluation of experimental procedures for confined concrete columns using 3D finite element analyses - Koksal, H. O.; Karakoc, C.; Polat, Z.; Turgay, T.; Akgun, S. (WIT PRESS/COMPUTATIONAL MECHANICS PUBLICATIONS, 2007)
This paper presents the results of the early stages of both a continuing experimental work on the square confined concrete columns and their 3D finite element modeling based on the isotropic damage theory in order to establish a realistic approach for the confinement pressure. Based on the axial behavior of four RC columns with a 200 mm square cross section tested under concentric loading, existing experimental data and procedures in the literature are evaluated. As demonstrated from the comparison of the FE analysis and the test results, obtaining a uniform axial loading and deformation state is questionable.
Keywords: confinement pressure; reinforced concrete column; finite element; isotropic damage theory; geometrical defects; DUCTILITY; STRENGTH; MODEL; Engineering; Mechanics